PENDIDIKAN PERDAMAIAN TRANSFORMATIF: ANALISIS PSIKOANALISIS ATAS BIOGRAFI MAULANA WAHIDUDDIN KHAN - Zaenal Abidin; Muhammad Taufik Ismail (Universitas Muhammadiyah Surakarta, 2021)
One of the problems of religious education in the post truth era is how religion is internalized as well as actualized, so that the character that is formed is a divine character. This is a classic problem, religion apart from coming as a savior, liberator, is also often misinterpreted as a different command to fight and destroy. India is an example of a country with high vulnerability to religious conflict. But in the midst of the complexity of the conflict, a figure for peace emerged, Maulana Wahiduddin Khan. Khan's peaceful personality did not emerge from a vacuum, there was a long process in its formation. By reflecting on Khan's way of life, it is hoped that he will be able to take values to contribute to peace education, especially building divine character. With the analytical knife of Lacan's psychoanalysis, this study attempts to portray how a peaceful person is transformed. The results of the study show that Khan underwent two transformations, first, the Ad-Dhuha moment, as a sign of leaving agnostic, towards full faith. Second, leaving Jemaah Islamiah, Jamaah Tabligh, to build their own movement. Khan's transformation process did not go smoothly, there was a struggle intrapsychologically, interpsychologically, to be able to achieve personal peace. An important aspect of the results of this study is how teachers are able to become transformative facilitators who help their students reach maturity in knowledge, spirituality, and divine character